Evaluations of Swedish Labor Market Policy - Anders Björklund (The Research Institute of Industrial Economics (IUI), 1989)
Sweden has for a long time spent large resources on labor market policies targeted to the unemployed. In the Anglo-Saxon labor economics literature new methods have been developed for the purpose of estimating the effects of such policies. This paper presents the new methods in this field and describes the main studies of Swedish labor market policies. The conc1usion is that in spite of new methodological insight there remains much uncertainty about the effects of the Swedish policy experiment.
Keywords: J08; O52; 330; Labour market policy; Sweden